2018
DOI: 10.1177/2396987318775206
|View full text |Cite
|
Sign up to set email alerts
|

Oral care after stroke: Where are we now?

Abstract: There appears to be an association between poor oral hygiene and increased risk of aspiration pneumoniaa leading cause of mortality post-stroke. We aim to synthesise what is known about oral care after stroke, identify knowledge gaps and outline priorities for research that will provide evidence to inform best practice. Methods: A narrative review from a multidisciplinary perspective, drawing on evidence from systematic reviews, literature, expert and lay opinion to scrutinise current practice in oral care aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 60 publications
0
33
0
1
Order By: Relevance
“…Several studies have demonstrated that oral care is associated with a decreased incidence of aspiration pneumonia in elderly people [26][27][28]. We earlier reported that a systematic oral care program for patients with HNC may improve treatment compliance by decreasing the risk of infection [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that oral care is associated with a decreased incidence of aspiration pneumonia in elderly people [26][27][28]. We earlier reported that a systematic oral care program for patients with HNC may improve treatment compliance by decreasing the risk of infection [29].…”
Section: Discussionmentioning
confidence: 99%
“…As the dental examinations took place within 24 h of inpatient admission, these results cannot be attributed to insufficient oral care during hospitalization at the stroke unit. On the contrary, it is wellknown that nursing-driven oral hygiene care may be of poor quality during hospitalization, particularly in dependent patients, with oral care procedures often being delegated to the least qualified members of the nursing team (61,62). Consequently, Wagner et al found that implementation of a systematic oral hygiene program significantly reduced incidence of strokeassociated pneumonia in acute stroke patients (63).…”
Section: Dental and Oral Datamentioning
confidence: 99%
“…However, patients who are exclusively fed via the enteral route are also at risk of developing SAP. Tube feeding [13] and poor oral hygiene [14] may increase the risk of pneumonia by promoting bacterial colonization of the oropharynx. The presence of oral and dental disease causes alterations of oropharyngeal flora, and reduced saliva flow increases the bacterial density of the saliva.…”
Section: Introductionmentioning
confidence: 99%